Cognitive Boundaries of Metaphorical and Literal Language: Insights from Autism Spectrum Disorder (ASD) (Signifiances (Signifying), 2026)
This meta-study explores the boundaries between metaphorical and literal language, with the aim of contributing to a better understanding of what is meant when referring to metaphors. It reviews a key embodied theory that addresses metaphorical processing, enaction theory, and investigates why certain neurodivergent groups, such as individuals with autism spectrum disorder (ASD), are reported to experience difficulties with metaphorical language. The findings suggest that literal and metaphorical language are processed similarly, which might explain why there is still no consensus on what constitutes a metaphor, an ongoing issue in linguistic research. Metaphors may lack enough inherent features to be classified as an objectively distinct cognitive-linguistic category.